2021
DOI: 10.3758/s13415-020-00858-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Emotion and Self-reference in Source Memory: An ERP Study

Abstract: The way emotional information is encoded (e.g., deciding whether it is self-related or not) has been found to affect source memory. However, few studies have addressed how the emotional quality and self-referential properties of a stimulus interactively modulate brain responses during stimulus encoding and source memory recognition. In the current study, 22 participants completed five study-test cycles with negative, neutral, and positive words encoded in self-referential versus non-self-referential conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 143 publications
(303 reference statements)
0
5
0
Order By: Relevance
“…However, Sui & Zhu used a free recall paradigm which, as previously mentioned, may result in different behavior than the present recognition design. Furthermore, some studies looking at source memory have found diminished SREs depending on the valence and nature, for example, spatial location versus color, of source details (Durbin et al, 2017;Pereira et al, 2019Pereira et al, , 2021Yin et al, 2019), further indicating the existence of task-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sui & Zhu used a free recall paradigm which, as previously mentioned, may result in different behavior than the present recognition design. Furthermore, some studies looking at source memory have found diminished SREs depending on the valence and nature, for example, spatial location versus color, of source details (Durbin et al, 2017;Pereira et al, 2019Pereira et al, , 2021Yin et al, 2019), further indicating the existence of task-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, for the self-mother group, because they are Western participants, we expected an object mSRE such that recognition and source memory accuracy should be higher for self-than for mother-referenced objects. While Cunningham et al, 2013Cunningham et al, , 2014Pereira et al, 2021) have taken account of these differences in response mode and the refined information it generates about recall.…”
Section: The Present Studymentioning
confidence: 99%
“…Some object mSRE studies have used a source-specific recognition task where participants responded 'Me,' 'Other', or 'New' during the memory test (Cunningham et al, 2011, Experiment 3;Cunningham et al, 2013;Cunningham et al, 2014;Pereira et al, 2021). Cunningham et al (2011) calculated sensitivity (d') based on unique self-owned and other-owned false alarm rates.…”
Section: The Present Studymentioning
confidence: 99%
“…Besides, contextual expectancies may alter word emotional understanding with stronger P200 and LPP responses when words are embedded into congruent emotional contexts (Chou et al, 2020). What is more, selfreferencing contexts may enhance emotional perception [see (Herbert et al, 2011) for effect on LPP amplitude], without which negative common words may hinder source memory performance, underscored by the absence of old/new item effect on ERP amplitude between 500 and 800 ms (Pereira et al, 2021). In sum, by highlighting the relevance of the whole epoch to link neuronal processing to behavioral emotional perception, our correlational analysis may have emphasized the interactive interplay between several representational levels during online emotional speech comprehension.…”
Section: Electroencephalographic Time Course Differentially Encodes D...mentioning
confidence: 99%